Performance evaluation of multi-stage and multi-pass reverse osmosis networks for the removal of N-nitrosodimethylamine -D6 (NDMA) from wastewater using model-based techniques. Issue 4 (August 2018) - Al-Obaidi, M.A.; Kara-Zaïtri, C.; Mujtaba, I.M.
Highlights: The simulation and optimisation studies are based on a developed model for RO. A novel multi-pass RO process design for removal NDMA from wastewater is proved. The permeate reprocessing design of RO process enhances the removal of NDMA. A viable value of 92.5% of NDMA removal is achieved at reasonable recovery of 40%. Abstract: The removal of pollutants such as N -nitrosamine present in drinking and reuse water resources is of significant interest for health and safety professionals. Reverse osmosis (RO) is one of the most promising and efficient methodologies for removing such harmful organic compounds from wastewater. Having said this, the literature confirms that the multi-stage RO process with retentate reprocessing design has not yet achieved an effective removal of N -nitrosodimethylamine-D6 (NDMA) from wastewater. This research emphasizes on this particular challenge and aims to explore several conceptual designs of multi-stage RO processes for NDMA rejection considering model-based techniques and compute the total recovery rate and energy consumption for different configurations of retentate reprocessing techniques. In this research, the permeate reprocessing design methodology is proposed to increase the process efficiency. An extensive simulation analysis is carried out using high NDMA concentration to evaluate the performance of each configuration under similar operational conditions, thus providing a deep insight on the performance of the multi-stage RO permeate reprocessing predictive design. Furthermore, an optimisation analysis is carried out on the final design to optimise the process with a high NDMA rejection performance and the practical recovery rate by manipulating the operating conditions of the plant within specified constraints bounds. The results show a superior removal of NDMA from wastewater.